2019
DOI: 10.1186/s12870-019-1732-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of the chloride channel gene, GsCLC-c2 from wild soybean

Abstract: Background The anionic toxicity of plants under salt stress is mainly caused by chloride (Cl − ). Thus Cl − influx, transport and their regulatory mechanisms should be one of the most important aspects of plant salt tolerance studies, but are often sidelined by the focus on sodium (Na + ) toxicity and its associated adaptations. Plant chloride channels (CLCs) are transport proteins for anions including Cl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 49 publications
2
58
1
Order By: Relevance
“…Glycine cyrtoloba is a wild soybean species native to saline soil in Australian beach, and a series of studies have demonstrated its high salt tolerance in terms of inhibiting Na + accumulation, photosynthetic activity, antioxidant activity, cyclic electron flow around PSI and excitation energy dissipation [23,[34][35][36]. In China, a halophytic soybean, Glycine soja, grows in coastal saline land in Yellow River Delta, and similar to Glycine cyrtoloba, Glycine soja also can effectively retard toxic ions accumulation and maintain high photosynthetic activity under salt stress [24,37,38]. In a recent study, we systematically illustrated salt tolerance in Glycine soja from the aspects of root ions flux, antioxidant system, osmotic regulation and photosynthesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Glycine cyrtoloba is a wild soybean species native to saline soil in Australian beach, and a series of studies have demonstrated its high salt tolerance in terms of inhibiting Na + accumulation, photosynthetic activity, antioxidant activity, cyclic electron flow around PSI and excitation energy dissipation [23,[34][35][36]. In China, a halophytic soybean, Glycine soja, grows in coastal saline land in Yellow River Delta, and similar to Glycine cyrtoloba, Glycine soja also can effectively retard toxic ions accumulation and maintain high photosynthetic activity under salt stress [24,37,38]. In a recent study, we systematically illustrated salt tolerance in Glycine soja from the aspects of root ions flux, antioxidant system, osmotic regulation and photosynthesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…In other plants, many CLC genes are involved in anions transport and in the response to salt stress. For instance, the expression level of OsCLC-1 is upregulated in rice under NaCl stress [ 22 ]; PtrCLC genes are profoundly induced in orange by salt stress [ 23 ]; GmCLC1 has been found to enhanced salt tolerance in transgenic Arabidopsis seedlings by reducing the Cl − accumulation in shoots [ 36 ]; and GsCLC-c2 over-expression contributes to Cl − and NO 3 − homeostasis, and therefore confers the salt tolerance on wild soybean [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis plants, AtCLC genes are involved in salt tolerance [ 44 , 45 ]. Also, in wild soybean BB52, the GsCLC- C2 gene expresses in the roots and functions in Cl − sequestration in roots, which contributes to lowering Cl − transportation from roots to shoots [ 46 ]. Further studies are necessary to determine the physiological role of OsCLC2 in leaf sheath using OsCLC2 -knockout or overexpressed rice mutants and validate if the difference in OsCLC2 expression levels causes the genotypic variation in the Cl − removal ability in rice leaf sheaths.…”
Section: Discussionmentioning
confidence: 99%